The relationship between pleural effusion index and mortality in children with dengue shock syndrome - Novianti Hawarini; Muhammad Sholeh Kosim; Mohammad Supriatna; Yusrina Istanti; Eddy Sudjanto (Indonesian Pediatric Society, 2012)
Background Dengue shock syndrome (DSS) mortality rate is stillhigh. The extent of plasma effusion in dengue shock syndromecan be identified in the right lateral decubitus position on chestxô€ƒray, and quantified by the pleural effusion index (PEl). It isthought that PEl value can be used to predict DSS mortality inchildren. Pleural effusion in DSS patients can cause respiratoryfailure and death.Objective To determine the relationship bet ween PEl andmortality in children lith DSS.Methods This crossô€ƒsectional, retrospective study was held in theDr. Kariadi Hospital, Semarang, Indonesia. Data was taken frommedical records of pediatric intensive care unit (PICU) patientswith DSS from January 2009 to January 2011. DSS diagnosiswas confirmed by clinical and radiological manifestations. PEldiagnosis was established by the presence of fluid in the pleuralcavity on pulmonary radiological examinations. Xô€ƒrays wereinterpreted by the radiologist on duty at the time. Chi square andlogistic regression tests were used to analyze the data.Results There were 48 subjects with DSS, consisting of 18 males(37.5 %), and 30 females (62.5%). Twentyô€ƒnine subjects (60.4%)survived and 19 (39.6%) died. One patient (2.1 %) had PEl <6%,4 (8.3%) had PEl 6-15%, 17 (35.4%) had PEl 15-30%, and26 (54.2%) had PEl> 30% on their xô€ƒrays. The mortality rateof DSS with PEl 15-30% was 11.8% (95% CI 0.021 to 0.564;P<0.005) and PEl >30% was 65.4 % (95% CI 3,581 to 99,642;P <0.005).Cone-lution PEl> 15% was a risk factor for mortality in childrenwith DSS. [Paediatr lndanes. 2012;52:239-42].